The Influence of Irrational Thinking and Social Networks on Citizenship Values for Undergraduate Students in Sultanate of Oman - Al-Shuaili, Moosa Sulieman (Journal of Educational and Psychological Sciences, 2023)
This research seeks to explore the influence of irrational thinking and social networks on citizenship values for undergraduate students in the Sultanate of Oman. The researcher adopted the descriptive analytical approach. The study sample consisted of 900 male and female students from: Sultan Qaboos University, Arab Open University and the Modern College of Business and Science. For the purpose of collecting the data, the researcher used the questionnaire method. To analyze the data, the researcher applied the mathematical average, standard deviations, frequencies, percentages, t-test, Pearson's correlation coefficient, and multiple regression coefficient. The findings concluded that the influence of social media on the citizenship values from the perspective of the population was high; as the average effect achieved 3.86, and the spread of rational thinking was high, compared to irrational thinking which achieved low score with an average of 1.45. There is a positive relationship between the degree of use of social networks and the level of influence on citizenship values and the spread of rational thinking among undergraduate students. There were statistically significant differences regarding the degree of using social networks in favor of female students and public universities, as well as differences in the level of influence on the values of citizenship in favor of female students, and differences in the degree of the spread of rational thinking in favor of the type of university and years of study. Consequently, the findings pointed out that it is possible to predict the effect of the research independent variables on the dependent variable (the level of citizenship values) The research recommended the necessity of activating student counseling institutions in modifying students' ideas.
Keywords: Irrational thinking; citizenship values; undergraduate students